Hubungan Belajar Dari Rumah Dan Peningkatan Berat Badan Pada Anak Usia Sekolah Di Masa Pandemi Covid 19 - Nourmayansa Vidya Anggraini; Serri Hutahaean; Utami Wahyuningsih; Nur Fitriah Efendy (Jurnal Keperawatan Muhammadiyah, 2021)
Objective: The Indonesian government officially announced that COVID-19 had entered Indonesia in early March 2020. The COVID-19 pandemic has changed all aspects of life, one of which is the world of education. Learning is still carried out but is carried out from home, or another name is the school from home (SFH). This SFH condition causes a lack of physical activity and increases the sedentary lifestyle among school students. Methods: This study uses a descriptive method with data collection techniques using a questionnaire in Google Form. The number of samples is 242 students. The results of the data collected were analysed and processed using SPSS 25.0. Data analysis using Chi-Square Test.Results: The data analysis results showed a relationship between learning from home and weight gain of elementary school students with a p-value <0.005, namely a p-value of 0.046.Conclusion: Based on the results of this study, it is recommended for parents and teachers always to accompany and remind school children to maintain a healthy diet. Moreover, physical activity is needed even though learning from home so that the child's weight does not increase significantly and remains within the criteria for normal nutritional status. In addition, it is also recommended to conduct other studies related to factors that influence weight gain in school-age children during the covid-19 pandemic.